The Society of Jesus in Ireland, Scotland, and England, 1589-97 : building the faith of Saint Peter upon the King of Spain's monarchy /: building the faith of Saint Peter upon the King of Spain's monarchy. (2016) - McCoog, Thomas M; S. J
No abstract available